Specters of Causality - Florian Sprenger (Media Theory, 2022)
Electricity is invisible, only its effects can be perceived, but they should not be mistaken for electricity itself, because electricity designates a condition of matter. The article describes how in eighteenth century electricity research, the aesthetics of electricity – the forms in which it appears and its representations – are haunted by the anaesthetics of its object. It investigates one specific challenge in the early history of electricity research, in which questions of mediation, aesthetics, perceivability and causality are fundamentally connected: attempts to measure the speed of electric transmissions through wires. The article describes these phenomena as ‘specters of causality’, that means forces that become perceivable only in the form of aesthetic effects which cloak the physical events which happen in the realm of the invisible. Specters of causality made imperceptibility perceptible. These ghosts of mediation materialized the invisible transmission of electricity as an aesthetic experience. The causality that connects actions with effects at a distance through a wire challenges the perceptual status of immediacy and mediation.